Aspirin or Ticagrelor in Staphylococcus aureus Infective Endocarditis: Where Do We Stand? - Leeten, Kirsten; Jacques, Nicolas; Lancellotti, Patrizio; Oury, Cécile (Frontiers in Cell and Developmental Biology, 2021)
Infective endocarditis is a challenging disease with a high mortality and morbidity rate. Antibiotic prophylaxis is currently recommended in high-risk infective endocarditis patients. However, the use of antibiotics faces the challenge of a low efficacy and contributes further to the emerging infection rate by antibiotic-resistant strains, emphasizing the need for new therapeutic strategies. Platelets are essential in the initial phase of infective endocarditis, acting as first-line immune responders. During the first phase of disease, bacteria can interact with platelets and counteract platelet antimicrobial activities. Mechanistic in vitro and animal studies on the effect of aspirin on bacteria-platelet interactions and the prevention of vegetation development showed promising results. However, data from clinical studies on the outcome of infective endocarditis patients who were receiving medically indicated aspirin therapy remain controversial. Therefore, the benefit of antiplatelet agents in infective endocarditis prevention has been questioned. Besides aspirin, it has been discovered that the platelet P2Y12 receptor antagonist ticagrelor has antibacterial properties in addition to its potent antiplatelet activity. Furthermore, a recent study in mice and a case report remarkably indicated the ability of this drug to eradicate Staphylococcus aureus bacteremia. This review will focus on current knowledge on antibacterial activity of ticagrelor, compared to aspirin, pointing out main unanswered questions. The goal is to provide food for thought as to whether a prior ticagrelor therapy might be beneficial for the prevention of infective endocarditis.